SUBSTITUSI JAGUNG DAN AMPAS KURMA DALAM RANSUM KOMERSIAL TERHADAP PERSENTASE GIBLET DAN LEMAK ABDOMEN AYAM PEDAGING - swito, swito; sudrajat, Deden; handarini, Ristika (Jurnal Peternakan Nusantara, 2015)
Dates press cake is a waste product a date syrup industry which is potensial to be used as animal feed. This research was aimed to study the effects of corn substitution with date press cake in commercial ration on the percentage of giblet and abdominal fat of broiler. The study was conducted at the Trial Farm of the Department of Animal Science, Faculty of Agriculture, University of Djuanda, Bogor from 17 February to 16 March 2014. One hundred and five one of day old Cobb Slouw chicks were used in this research. The chickens were fed commercialRation BR 0, BR 1 and the combination of corn and dates press cake. The design of research was used a completely randomized design with 7 treatments and 3 replications. The treatments were: 100% commercial ration (R0, as control), 97.5% commercial ration added 2,5% corn (R1), 97.5% commercial ration added 2,5% dates press cake (R2), 95% commercial ration added 5% corn (R3), 95% commercial ration added 5% dates press cake (R4), 92,5% commercial ration added 7,5% corn (R5) and 92,5% commercial ration added 7,5% dates press cake (R6). The data were analyzed by ANOVA and Duncan test. The results showed that treatments did not give any signicant effect on all of parameters ie: slaughter weight, percentage of giblet and percentage of abdominal fat. It was concluded that dates press cake could be used up to 7.5% in commercial ration of broiler